The News Construction Of Women In Online Media Tirto.Id About Cases Of Sexual Abuse - Bunga Wahyu Kartikasari; Arif Wibawa; Prayudi Prayudi (Jurnal Ilmu Komunikasi, 2019)
There are many mass media in Indonesia which is not implementing the concept of equality gender yet, especially news about sexual harassment. This research focuses on the news framing in online media Tirto.id under the hashtag sexual harassment. Constructivism theory is used in this research which is emphasized the reality is plural and subjective. This research using Robert Entman’s framing method, the researcher takes 18 from 67 articles to be analyzed. Entman’s method focuses on four things, problems identification, casual interpretation, make moral judgment dan treatment recommendation. The result of this research is Tirto.id already implemented gender perspective journalism which was not brought the woman down but also didn’t blame the men. Tirto.id constructs women like the one who’s equal, smart and independent, but there’s an inequality of gender between men and women. That’s why women are kind of powerless that make them a victim of sexual harassment. For the news in the celebrity corner, Tirto.id tried to educate readers on how to respond to the sexual harassment. Meanwhile, in the non-celebrity corner, there are many critics said to the related institution as the way to enforce the concept of gender equality. This study provides recommendations in the form of policy proposals for online media to implement policies like Tirto.id's in delivering news, namely clear, bright, insightful, contextual, in-depth, factual and investigative like Tirto.id.